2021
DOI: 10.3390/life11090868
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Silencing of HER2 Expression during Epithelial-Mesenchymal Transition Leads to Trastuzumab Resistance in Breast Cancer

Abstract: HER2 receptor tyrosine kinase (encoded by the ERBB2 gene) is overexpressed in approximately 25% of all breast cancer tumors (HER2-positive breast cancers). Resistance to HER2-targeting therapies is partially due to the loss of HER2 expression in tumor cells during treatment. However, little is known about the exact mechanism of HER2 downregulation in HER2-positive tumor cells. Here, by analyzing publicly available genomic data we investigate the hypothesis that epithelial-mesenchymal transition (EMT) abrogates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…Previously, we and others reported that long-term exposure to MPE/MA led to epithelial-mesenchymal transition (EMT), antigen loss, as well as treatment resistance. 16 , 31 To exclude the potential influence of continuous exposure to MPE/MA, such as HER2 antigen loss, we cultured SKOV3 PD-L1 cells in MA-supernatant from an OSC patient (Pt4) for 1 month (MA-treated SKOV3 PD-L1 ), and found that the levels of HER2 and PD-L1 expressions were similar on MA-treated and untreated SKOV3 PD-L1 cells (Fig. 2c and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we and others reported that long-term exposure to MPE/MA led to epithelial-mesenchymal transition (EMT), antigen loss, as well as treatment resistance. 16 , 31 To exclude the potential influence of continuous exposure to MPE/MA, such as HER2 antigen loss, we cultured SKOV3 PD-L1 cells in MA-supernatant from an OSC patient (Pt4) for 1 month (MA-treated SKOV3 PD-L1 ), and found that the levels of HER2 and PD-L1 expressions were similar on MA-treated and untreated SKOV3 PD-L1 cells (Fig. 2c and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the H3K9ac and H3K27me3 epigenetic profiles and microanalysis of genes enriched with the promoter h3k9ac chip revealed epi-promoter regions of genes modified by mark at HER2+ and TNBC tumors. The H3K9ac modification has been reported to induce downregulation of most of the related genes in HER2-amplified tumors [74]. Descriptive investigations of the HER2/neu epigenetics in BC support the repression of Her2/neu by increased H3K9me2.…”
Section: Her2(+) Breast Cancermentioning
confidence: 94%
“…Studies have shown that approximately 60% to 70% of patients with HER2‐positive BC develop resistance to trastuzumab due to the cleavage and shedding of HER2. The induction of epithelial‐mesenchymal transition (EMT) in HER2‐overexpressing epithelioid BC cells can lead to the down‐regulation of HER2 expression through the epigenetic silencing of ERBB2 gene in chromatin, forming a “HER2 negative” subtype, thereby reducing the binding rate of trastuzumab to cells and leading to the resistance of trastuzumab 79 . Therefore, the prognosis and drug tolerance of HER2 positive and negative patients may be improved by EMTs in the future.…”
Section: Treatment Of Her2‐low/zero Breast Cancermentioning
confidence: 99%